SINERGITAS STAKEHOLDER DALAM PROGRAM KAMPUNG TEMATIK KULINER DI KELURAHAN JATINGALEH KOTA SEMARANG - Sekar Mutiara Mashita; Dewi Rostyaningsih; Hesti Lestari (Journal of Public Policy and Management Review, 2023)
The implementation of the Culinary Thematic Village Program, shows that there is no involvement of the private sector, lack participation of younger generation, and parents domination in the community. This study aims to describe and analyze stakeholder synergy and the inhibiting factors, in the implementation of the Culinary Thematic Village Program in Jatingaleh Village, Semarang City. The research method used is descriptive qualitative. The results show that stakeholder synergy hasn’t gone well. The society are less active in providing feedback, and coordination isn’t effective. Factors inhibiting stakeholder synergy is, human resources, budget constraints, and role domination in society. The conclusion is, communication hampered by the inactivity society in providing feedback. Coordination hasn’t been effective, due to a lack community commitment, competence, and awareness, lack of optimal coordination continuity, and role dominance from RW. The conclusion is, open discussion forums, develop closer interpersonal relationships, hold meetings for all stakeholders, conduct comprehensive and routine education for society, increase promotion, seek funding assistance, and provide opportunities for society according to their respective roles.